Cognitive and neuromodulation strategies for unhealthy eating and obesity: Systematic review and discussion of neurocognitive mechanisms. (April 2018) - Forcano, Laura; Mata, Fernanda; de la Torre, Rafael; Verdejo-Garcia, Antonio
Highlights: 6 Cognitive and 4 Neuromodulation strategies to reduce unhealthy eating identifed. Response inhibition and goal-oriented trainings reduce BMI and unhealthy eating. Stimulation of DLPFC and lateral hypothalamus reduce food craving and intake. Studies quality moderately high, but longer duration trials in clinical groups needed. Interventions targeting cognitive control are promising for obesity treatment. Abstract: We systematically reviewed research on cognitive training and neuromodulation interventions for reducing food craving/intake, unhealthy diet and weight, and discussed their mechanisms of action. We reviewed 50 studies involving six cognitive trainings: Approach and Attentional Bias Modification, Implementation Intentions, Response Inhibition, Episodic Future Thinking and Working Memory; and four neuromodulation approaches: Transcranial Magnetic Stimulation (TMS), transcranial Direct Current Stimulation (tDCS), Deep Brain Stimulation (DBS) and Neurofeedback. Response Inhibition and Implementation Intentions have shown to reduce unhealthy diet and weight in people with overweight/obesity. Attentional Bias Modification has shown promising results in healthy-weight participants. Brain stimulation of the Dorsolateral Prefrontal Cortex via tDCS and the Hypothalamus via DBS showed benefits for reducing food craving and weight in people with overweight/obesity. Studies quality was generally high, but most trials were short-term and many conducted in healthy-weight samples. Modification of cognitive control and motivational processes/circuits are common mechanisms of beneficial training and neuromodulation interventions, and thus a promising approach for overweight/obesity treatment. Longer duration trials in clinical populations are needed to confirm benefits.